Enteritis necroticans pada ayam broiler akibat infeksi sekunder clostridium perfringeens Tipe A - Agus Setiyono; Rachmat Nabib; Gatut Ashadi; Aisjah Girinda; Lily Natalia (Hemera Zoa, 1993)
The experiment was conducted to determine the relationship between conccidiosis vaccination and secondary infection of Clostridium perfringens type-A as a cause of Enteritis Necroticans in broiler chickens.The completely randomized design was used in this experiment. In this study 102 Arbor Acres strain unsexed chicken were randomly assigned to 8 treatment groups with 12 chicks each. Feed and water were given ad libitum.Treatment factors in this experiment were coccidiostat (Salinomycin 6%), coccidiosis vaccine and Clostridium perfringens type-A isolate, and their combinations.The anatomy pathology (AP) and histopathology (HP) figures of the chicken intestines were evaluated.Histopathology results indicated that the relationship between coccidiosis vaccination and secondary infection of Clostridium perfringens type-A was highly significant (p < 0.01) but the anatomy pathology figures showed that the relationship was not significant (p < 0.05).